Problems Associated with the Determination of Risks in the Financial Markets - Taghiyev, Murad R. (Caucasus Journal of Social Sciences, 2023)
The article is devoted to the problem of measuring risks in financial markets. From various complex scientific definitions, it synthesizes an intelligent definition of entropy. Furthermore, risk is considered a probabilistic criterion, described in connection with the normal probability distribution. The next step suggests a method for calculating the risk index for practitioners not burdened with deep mathematical knowledge, using the covariance index and the determination of the Sharpe ratio. Recommendations are provided at the end of the article.